2010
DOI: 10.3109/09553002.2010.518209
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of asymmetric dimetilarginine (ADMA) levels in cardiac and gastrocnemius muscles following radioactive iodine application in guinea pigs and the effect of L-carnitine on this alteration

Abstract: Our results indicated that RAI appears to exert an inhibitory effect on ADMA and SDMA levels of ventricular muscle. LC administration when given adjuvant to RAI therapy may cause a marked decrease in ADMA concentrations of both ventricular and gastrocnemius muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A study of lipid metabolism in radiation-exposed individuals manifested persistent dyslipidemia associated with IR (Wong 2014; Hayashi et al 2003). Asymmetric dimethylarginine (ADMA) levels in ventricle muscle of guinea pigs treated with radioactive iodine 131 I in a total dose of 1.11 × 10 6 kBq −1 kg −1 were shown to decrease (Vardar et al 2011). Experimental and clinical studies also observed a correlation between the increased ADMA levels in blood plasma and the endothelial dysfunction (Loland et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A study of lipid metabolism in radiation-exposed individuals manifested persistent dyslipidemia associated with IR (Wong 2014; Hayashi et al 2003). Asymmetric dimethylarginine (ADMA) levels in ventricle muscle of guinea pigs treated with radioactive iodine 131 I in a total dose of 1.11 × 10 6 kBq −1 kg −1 were shown to decrease (Vardar et al 2011). Experimental and clinical studies also observed a correlation between the increased ADMA levels in blood plasma and the endothelial dysfunction (Loland et al 2013).…”
Section: Introductionmentioning
confidence: 99%